Pesan Propaganda Rasisme Film “8 Mile” - Nathan Tjhai; Sinta Paramita (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2019)
Racism is used to define people based on perceptions of physical differences that imply genetic differences. Racism has become a social and cultural fact and this can be used to justify policies and discrimination and affect the lives of both the majority and minority races. This study uses Charles's theory, where this theory is famous for its triangles of meaning, namely signs, objects and interpretan to study the film